2011
DOI: 10.1177/0883073811419256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Associations of Occipital Intermittent Rhythmic Delta Activity

Abstract: Association of occipital intermittent rhythmic delta activity with absence seizures has been well documented in the published literature. Two recent studies have also described an association with focal seizures. After obtaining approval from our Institutional Review Board, all electroencephalograms with occipital intermittent rhythmic delta activity at our institution between July 1, 2006 and December 31, 2009 were identified. Charts of these patients were reviewed to collect clinical data. A matched comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Gullapalli and Fountain [6] found that the most frequent convulsive episodes in patients with OIRDA are generalized tonic-clonic and absence episodes. Thirty percent of epileptic discharges occur in epileptic patients as compared to 12.5% in patients without convulsive episodes [6,12]. Occipital intermittent delta activity in most patients occurs during wakefulness and hyperventilation [8], as in our case.…”
Section: Discussionsupporting
confidence: 54%
“…Gullapalli and Fountain [6] found that the most frequent convulsive episodes in patients with OIRDA are generalized tonic-clonic and absence episodes. Thirty percent of epileptic discharges occur in epileptic patients as compared to 12.5% in patients without convulsive episodes [6,12]. Occipital intermittent delta activity in most patients occurs during wakefulness and hyperventilation [8], as in our case.…”
Section: Discussionsupporting
confidence: 54%
“…[3] In another study, Desai et al studied 31 cases and found that absence seizures were more frequently seen in patients with OIRDA. [8] In our patient, the main clinical picture consisted of periods of frequent and serious visual hallucinations and severe headache. Visual hallucinations may be major symptoms of occipital lobe epilepy as well as migraine aura.…”
Section: Discussionmentioning
confidence: 65%
“…In accordance with the American Clinical Neurophysiology Society’s standardized critical care EEG terminology (2021 version), Rhythmic Delta Activity (RDA) is defined as a waveform with relatively uniform morphology and duration, without an interval between consecutive waveforms, and a frequency of 0.5 to ≤4.0 Hz [15] . Although OIRDA has been documented previously in cases of focal epilepsies [14] in addition to CAE, repeat studies have not corroborated this as a statistically significant correlation [13] . Our case series, albeit limited in number, illustrates the presence of OIRDA in children with focal epilepsies and some atypical features as compared to that published in cases of CAE.…”
Section: Discussion/conclusionmentioning
confidence: 78%
“…OIRDA appears to be a relatively rare finding, with rates being reported between 0.75% [13] to 3.4% [14] of studies showing this finding. Given the relative rarity of OIRDA, and potential pathophysiological implication, further studies are necessary to determine if a correlation exists between OIRDA spatial distribution and localization, epileptiform features, cortical versus subcortical origin, or if this proposed link between CECTS/PS, and OIRDA represents a temporal progression or resides on a spectrum of focal and generalized abnormalities when OIRDA is seen in these patients.…”
Section: Discussion/conclusionmentioning
confidence: 93%
See 1 more Smart Citation